Ecological status assessment using periphytic diatom communites - case study Krka River - Žutinić, Petar; Kulaš, Antonija; Levkov, Zlatko; Šušnjara, Mirela; Orlić, Sandi; Kukić, Stefani; Goreta, Gordana; Gligora Udovič, Marija (Macedonian Journal of Ecology and Environment, 2020)
In the light of ever-growing issue of climate changes, a special focus has been directed towards freshwater periphytic algal communities. Diatoms, a commonly dominant group of protists in periphytic assemblages, are frequently used for ecological water-quality assessments of rivers. Diatom-based indices for ecological status assessment are based on a weighted-averaging model using relative abundances and the environmental optima of taxa. The aim of this study was to assess the ecological status of the Krka River based on taxonomic analyses of its periphytic communities. Sampling of periphytic and environmental variables was carried out in September 2017 and September 2018 on nine stations along the Krka River course, with 3 microhabitats at each station. Taxonomic analysis of samples in 2017 revealed a total of 120 diatom species, whilst in 2018 a total of 226 diatom species was noted. Ecological status of the Krka River, evaluated using TDIHR (Croatian Trophic Diatom Index) and the corresponding ecological quality ratio (EQR), was classified as high in most of the watercourse of the Krka River.